Constraining Late Quaternary Crustal Shortening in the Eastern Qilian Shan From Deformed River Terraces. Issue 9 (5th September 2020) - Zhong, Yuezhi; Xiong, Jianguo; Li, Youli; Zheng, Wenjun; Zhang, Peizhen; Lu, Honghua; Liu, Qingri; Lei, Jinghao; Chen, Gan; Gong, Zheng; Hu, Xiu; Zhang, Huiping
Abstract: The Qilian Shan, located in the northeastern Tibet, is under strong tectonic activity and earthquake motion due to the propagation of the plateau. At the mountain front of the eastern Qilian Shan, the Tongziba River, in the southern Zhangye Basin, flows northward and successively cuts the Minle‐Damaying Fault and the Yonggu Anticline, two parallel structures within the Frontal Thrust system of the Qilian Shan. Here we present a detailed record of seven strath terraces of this river that documents the history of active deformation of the two structures. Based on the estimated crustal shortening distance from the deformed terraces and the terrace formation age constrained by AMS 14 C and optically stimulated luminescence (OSL) dating, a horizontal slip rate of 1.4 ± 0.5 mm/year of the Minle‐Damaying Fault is constrained since 16.7 ± 1.8 kyr, and a shortening rate of 1.3 ± 0.4 mm/year across the Yonggu Anticline has been estimated in a similar time frame, respectively. In total, the shortening rate across the mountain front is estimated to be 2.7 ± 0.6 mm/year. GPS data show a similar modern shortening rate in this area, which indicates the rate of crustal shortening may be comparable in the modern and 10 4 ‐year scales. Our study supports a higher crustal shortening rate along the mountain front of the eastern Qilian Shan than that of the western Qilian Shan since the Late Quaternary. Key Points: The Minle‐Damaying Fault and the Yonggu Anticline have been active since at least 16.7 ± 1.8 kyr Estimated Late Quaternary shortening rate across the eastern Qilian Shan foreland is 2.7 ± 0.6 mm/year from terraces analysis Crustal shortening rate along the mountain front of the eastern Qilian Shan is probably higher than that of the western Qilian Shan